An evaluation of GMA's News and Public Affairs Library based on users' assessment - Maninang, Leilani P. (2003)
A descriptive survey was used to determine the current procedure/system implemented in the News and Public Affairs Library regarding the storage and retrieval of materials, evaluate it and determine its weakness through user's perception.